A Novel Hydraulic Simulation Platform of Multi-source and Multi-ring Experimental Heating Network. (2017) - Zhou, Shoujun; Li, Haiming; Wang, Tao; Gong, Pu
Abstract: In order to systematically and efficiently analyze the hydraulic condition of multi-source and multi-ring heating networks, this paper adopts MATLAB GUI to develop a novel hydraulic simulation platform for the built multi-source and multi-ring experimental heating network based on the proposed theory and method of simulation modeling, and the corresponding executable file is obtained. The new simulation platform could simulate operation and adjustment conditions of three typical network topologies, including single heat source and double rings, double heat sources and rings and three heat sources and rings. Combined with the experimental networks online monitoring system, the simulation platform could read real-time operation data of the experimental network and realize the real-time comparison and analysis between simulation and operation data. The simulation platform was designed with simple structure, user-friendly interface and easy accessibility so as to promote further efficient research on hydraulic conditions of multi-source and ring-shaped heating networks.